Separation, purification, regeneration and utilization of graphite recovered from spent lithium-ion batteries - A review. Issue 2 (April 2022) - Cheng, Qian; Marchetti, Barbara; Chen, Xuanyi; Xu, Su; Zhou, Xiao-Dong
Abstract: Vast consumption of lithium-ion batteries (LIBs) will produce a significant amount of spent graphite (SG). As a result, recovery and recycling of SG from spent LIBs becomes necessary and potentially cost-effective. If a good degree of crystallinity and the layered structure in SG are preserved, recycling of SG can represent an important secondary source of graphite. More importantly, the recovered SG may find its potential use as an active anode component to assemble a new LIB, provided that SG preserves a crystalline layered structure with the addition of a solid electrolyte interface layer, a slightly increased interlayer distance, and defects. Strategies for effective recovery of SG need to be developed due largely to a rapid increase in using LIBs in electric vehicles, large energy storage platforms and consumer electronics. In this review, we first discuss the separation and purification processes and technologies by highlighting their benefits and drawbacks, along with a few novel potential methods proposed. We will then elaborate new considerations into regeneration and future utilizations of recovered SG. Lastly, we offer our perspectives to highlight the environmental and economic benefits of graphite recycling. Graphical Abstract: ga1 Highlights: Advances in technologies for recycling graphite from spent LIBs are reviewed. Separation, purification, regeneration, and utilization of spent graphite are discussed. Advantages of structural characteristics of spent graphite were put forward. Environmental and economic benefits of graphite recycling are highlighted.